Cytotoxic mechanism of Bothrops jararaca venom mediated by mitochondrial depolarization - Ana Moira Morás; Luiza Steffens; Bruna Eliza Nordio; Jenifer Saffi; Eliane Dallegrave; Luciana Grazziotin Rossato-Grando; Dinara Jaqueline Moura (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2020)
Background: Snake venoms are natural sources of proteins and peptides with several biological activities. Therefore, this study aimed to evaluate the in vitro toxicity of crude Bothrops jararaca (B. jararaca) venom on different human tumor cells and investigate its action mechanism.  Material and methods: The crude venom from B. jararaca was provided by State Foundation for Health Research and Production and Center of Toxicological Information of Rio Grande do Sul, Brazil. To investigate different sensitivities of normal and cancer cell lines, cell viability was measured by using the MTT and neutral red uptake assays. Reactive oxygen species was measured by the oxidation of MitoSOX probe by superoxide anion in the mitochondria. Transmembrane mitochondrial potential was evaluated using Mitostatus probe incorporation. Genotoxicity evaluation was carried out by using alkaline comet assay. The activity of antioxidant enzymes, superoxide dismutase and Catalase (CAT), was assessed by measuring adrenochrome formation and absorbance of H2O2, respectively. To access the oxidative potential of crude venom, the oxidation of dichloro-dihydro-fluorescein diacetate probe and the adrenochrome formation were measured after incubation with the venom. Results: The acute treatment decreased in a dose-dependent manner the cell viability of HT-29, HCT116, MCF7 and HepG2 and the chronic exposition increased the cytotoxic effect (p>0.05) significantly. No differences in DNA damage or superoxide anion generation were observed in MCF7 cells after treatment. However, the mitochondrial membrane potential decreased and catalase activity increased after treatment in MCF7 cell line, indicating that the venom cytotoxicity could be due to the intrinsic apoptosis pathway mediated by mitochondrial damage and oxidative stress. Thus B. jararaca venom exhibited antitumor mechanism related to mitochondrial damage. Moreover, B. jararaca venom presented an oxidative potential in vitro.  Conclusion: These results contribute to understand the mechanism of action and suggest that snake venoms are a useful source to search new drugs with potential applications in cancer therapy.